Mabel and Sam at home - Urban, Linda (Chronicle Books, 2018)
Mabel and her younger brother Sam approach their new home and the trauma of moving by turning it into an adventure, imagining they are sailors approaching a new land, tour guides exploring a museum, and finally astronauts in space
Cover: One brave journey in three adventures
Keywords: Picture books / lcgft; Moving, Household -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Imagination -- Juvenile fiction; Dwellings -- Juvenile fiction; Moving, Household; Brothers and sisters; Imagination; Dwellings; Geschwister; Wohnungswechsel; Bilderbuch